Moderate morning rise in blood pressure has lowest risk of stroke but only in women - Head, G.A.; Sata, Y.; Imai, Y.; Kikuya, M.; Ohkubo, T.; Reid, Christopher; McGrath, B.M.; Lukoshkova, E.V. (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Background:The morning period which is recognized as the highest risk for cardiovascular events is associated with a surge in blood pressure (BP). However, it is unclear what aspect of this rise is important.Aim:To determine whether the rate of rise (RoR), the magnitude (day night difference) or the product [BP power (BPPower)] is associated with increased cardiovascular risk.Methods:We developed a logistic equation method to fit individual 24-h patterns of BP to determine RoR, amplitude and BPPower using the ambulatory recordings from the Ohasama study including 564 men and 971 women (16.6 years follow-up).Results:Men had a higher risk of cardiovascular events than women (24, 16%, P < 0.001). Age and night BP were strong linear risk predictors. In men sorting risk by quintiles of BPPower (adjusted for age, night BP, smoking status) revealed no clear linear or nonlinear pattern. However, in women BPPower had a U-shaped relationship with the lowest risk being the 2-3rd quintile for all cardiovascular events (Pquadratic = 0.01) including cardiovascular death (Pquadratic = 0.03) and nonfatal stroke (Pquadratic = 0.02). A similar but less clear trend was observed with the RoR but only stroke (infarct) reached significance (Pquadratic = 0.03) while sorting by range showed a U shaped pattern for combined cardiovascular events (Pquadratic = 0.04).Conclusion:These findings suggest that the morning BPPower is an important independent risk factor for predicting cardiovascular events and stroke but only in women with median levels having the lowest risk.